Association of HLA-A*02:01 type with efficacy and toxicity of immune checkpoint inhibitor therapy in melanoma patients: a retrospective cohort study - Isabel Manger; Christina Schmitt; Carola Berking; Lars E. French; Julio Vera-Gonzalez; Lucie Heinzerling (BMC Cancer)
Abstract Background Immune checkpoint inhibitors (ICI) are highly effective but may induce severe or even fatal and unpredictable immune-related adverse events (irAEs). It is unclear whether human leukocyte antigen (HLA) genes contribute to the susceptibility of developing irAEs during ICI therapy. Methods This multicentre retrospective study investigated the association of irAE and outcome with HLA-A*02:01 status in a cohort of 97 patients with metastatic melanoma undergoing ICI therapy. Organ-specific irAEs and therapy outcome as assessed by response rate, progression-free survival (PFS) and overall survival (OS) were analysed depending on HLA type HLA–A*02:01. For the outcome only patients with cutaneous melanoma were analysed. Chi square test, exact fisher test, Kruskal Wallis test and log rank test were employed for statistical analysis (p ≤ 0.05). Results The cohort included 38 HLA-A*02:01 positive (39.2%) and 59 HLA-A*02:01 negative (60.8%) patients. Data showed no evidence of an association of HLA-A*02:01 with organ-specific irAEs except for a numerical difference in immune-related colitis. Furthermore, response rates of the subgroup of patients with metastatic cutaneous melanoma did not differ between the two cohorts. The median PFS was 5 months and 8 months in HLA-A*02:01 positive and negative patients with cutaneous melanoma, respectively. Conclusion HLA-A*02:01 was not associated with specific checkpoint inhibitor-induced organ toxicity in this cohort of HLA-A-typed melanoma patients. Interestingly, in the relatively small subgroup of patients with cutaneous melanoma an earlier progression in HLA-A*02:01 positive patients was observed, however not in the long term. These findings are exploratory due to the limited sample size and require validation in larger, prospective cohorts.